1992
DOI: 10.1017/s0952523800004995
|View full text |Cite
|
Sign up to set email alerts
|

Contrast gain control in the primate retina: P cells are not X-like, some M cells are

Abstract: Primate retinal ganglion cells that project to the magnocellular layers of the lateral geniculate nucleus (M) are much more sensitive to luminance contrast than those ganglion cells projecting to the parvocellular layers (P). We now report that increasing contrast modifies the temporal-frequency response of M cells, but not of P cells. With rising contrast, the M cells' responses to sinusoidal stimuli show an increasing attenuation at low temporal frequencies while the P cells' responses scale uniformly. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
177
1
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(213 citation statements)
references
References 16 publications
32
177
1
3
Order By: Relevance
“…This might seem surprising in light of the correlation between mammalian ganglion cell types that show strong gain control and those that receive a large degree of amacrine cell input (Shapley and Victor, 1978;Freed and Sterling, 1988;Benardete et al, 1992;Kolb and Nelson, 1993;Weber and Stanford, 1994;Jacoby et al, 1996Jacoby et al, , 2000. Our results are consistent, however, with studies in salamander, which showed that gain control in ganglion cells can be explained primarily by gain control in presynaptic bipolar cells (Kim and Rieke, 2001;Rieke, 2001).…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…This might seem surprising in light of the correlation between mammalian ganglion cell types that show strong gain control and those that receive a large degree of amacrine cell input (Shapley and Victor, 1978;Freed and Sterling, 1988;Benardete et al, 1992;Kolb and Nelson, 1993;Weber and Stanford, 1994;Jacoby et al, 1996Jacoby et al, , 2000. Our results are consistent, however, with studies in salamander, which showed that gain control in ganglion cells can be explained primarily by gain control in presynaptic bipolar cells (Kim and Rieke, 2001;Rieke, 2001).…”
Section: Discussionsupporting
confidence: 47%
“…For example, primate midget (parvocellularpathway) ganglion cells lack gain control, and this is presumably explained not by their lack of specialized amacrine cell input, but rather by a lack of gain control in their presynaptic midget bipolar cell inputs (Benardete et al, 1992). Parasol (magnocellularpathway) ganglion cells show strong gain control, and this is presumably explained by gain control present in their presynaptic diffuse bipolar cell inputs (Jacoby et al, 1996(Jacoby et al, , 2000Benardete and Kaplan, 1999;Chander and Chichilnisky, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells with similar visual response properties, the Y-cells, were first observed more than forty years ago in the cat retina (Enroth-Cugell and Robson, 1966). The original observation of the cat Y-cells was followed by a decades-long search for the counterpart of these cells both in the primate retina and in the primate lateral geniculate nucleus (LGN) (de Monasterio, 1978;Kaplan and Shapley, 1982;Derrington and Lennie, 1984;Blakemore and Vital-Durand, 1986;Benardete et al, 1992;Levitt et al, 2001;White et al, 2002). Until this report, no clear evidence had been found for a distinct type of Y-like retinal ganglion cell in the primate.…”
Section: Introductionmentioning
confidence: 99%
“…Other major physiological differences reported between parvo-and magnocellular populations include contrast gain (Kaplan & Shapley, 1986;Croner & Kaplan, 1995) and contrast gain control (Benardete et al, 1992;Benardete & Kaplan, 1997. All these results were obtained for achromatic stimuli.…”
mentioning
confidence: 62%